2017
DOI: 10.1002/pits.22043
|View full text |Cite
|
Sign up to set email alerts
|

Use of a technology‐enhanced version of the good behavior game in an elementary school setting

Abstract: The purpose of this study was to investigate the effectiveness of a variation of the Good Behavior Game (GBG) in which teachers used ClassDojo to manage each team's progress. ClassDojo is a computerbased program that enables teachers to award students with points for demonstrating target behaviors. Dependent variables included class-wide disruptive and academically engaged behavior, teachers' ratings on the Behavior Intervention Rating Scale (BIRS), and the rate of teacher praise statements delivered in each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 33 publications
2
17
1
1
Order By: Relevance
“…To address these limitations, McHugh et al () recommended the addition of a technological component to traditional Tootling procedures. Similar to Lynne et al () in this study, ClassDojo was chosen as the technological component to be added to traditional classwide intervention. Researchers in this study found that tootling procedures using ClassDojo to report tootles reduced disruptive behaviors classwide with a large effect size, expanding on the research by McHugh et al ().…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…To address these limitations, McHugh et al () recommended the addition of a technological component to traditional Tootling procedures. Similar to Lynne et al () in this study, ClassDojo was chosen as the technological component to be added to traditional classwide intervention. Researchers in this study found that tootling procedures using ClassDojo to report tootles reduced disruptive behaviors classwide with a large effect size, expanding on the research by McHugh et al ().…”
Section: Discussionmentioning
confidence: 57%
“…The current study extended the literature by operationally defining the specific behaviors being observed and rewarded using the ClassDojo website. No previous studies had looked at ClassDojo in comparison to more traditional classwide interventions, but it had been used as an additional component to more traditional interventions, such as the GBG and Tootling (Lynne et al, ; McHugh, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations